(untitled) (Research, Society and Development, 2021)
Objective: to analyze the impacts on the quality of life of patients aged up to 12 years with atopic dermatitis and which are the main drugs used. Methods: An integrative literature review was used, using as a guiding question; “What are the impacts on the quality of life of patients aged up to 12 years with atopic dermatitis and what are the main drugs used?”. Results: the article resulted in the selection of 11 articles, of which more than half deal with reduced quality and the rest with new AD treatments. Conclusion: It can be seen a decrease in the quality of life of children and parents, also causing psychological and social damage. New alternatives such as Duplilumabe have been obtaining good results as an alternative to the treatment of AD is used when AD is not controlled by other conventional treatments or when in some cases conventional medications are not indicated. Herbal medicine demonstrated effectiveness in preventing AD, with Aloe Vera standing out due to its benefits.